Assessing the Diversity of Decapods (Crustacea: Malacostraca) With Environmental DNA ( eDNA ) in Coastal Water of Matang, Perak, Malaysia - Chuan‐Hui Lim; Sze‐Looi Song; Zulqarnain Bin Mohamed; Muhammad Fadhli Mat Sobri; Azmi Marzuki Muda; Saifullah Arifin Jaaman (Marine Ecology, 2025)
Decapods play vital ecological and economic roles, yet their diversity and distribution in the coastal waters of Matang remain poorly understood. Increasing anthropogenic pressures have further impacted their habitats, underscoring the need for improved biodiversity assessments. Conventional monitoring methods are often limited by inconsistencies, invasiveness, low taxonomic resolution, and inefficiency in complex habitats. This study evaluated the effectiveness of environmental DNA (eDNA) metabarcoding to assess decapod diversity in Matang waters. A total of 136 seawater samples were collected from predefined zones between October 2021 and October 2022. DNA was extracted using the CTAB method, and a partial mitochondrial cytochrome c oxidase subunit 1 (COI) gene region was amplified. The amplicons were sequenced using the Illumina MiSeq platform. This approach identified 12 decapod species from six families: Penaeidae (3 species), Lucideridae (1 species), Sergestidae (3 species), Dotillidae (1 species), Pilumnidae (1 species), and Diogenidae (3 species). Dominant species included Acetes japonicus (46%), Acetes indicus (27%), and Diogenes fasciatus (10.9%). Notably, eight species matched records from previous conventional surveys, while four additional taxa: 2 Diogenes spp. ( Diogenes fasciatus , Diogenes rectimanus ), a Dotillidae crab ( Ilyoplax serrata ), and a Pilumnidae crab ( Aniptumnus sp.) were newly detected in the area. These findings indicate that decapod richness in Matang is likely underestimated. In summary, eDNA metabarcoding offers a promising, non‐invasive alternative for biodiversity monitoring in dynamic environments and complements traditional methods. This study establishes a foundation for long‐term decapod monitoring and supports conservation efforts in the Matang region.